2020
DOI: 10.21608/ejhm.2020.114446
|View full text |Cite
|
Sign up to set email alerts
|

Results of Percutaneous Fixation of Acute Scaphoid Fractures by Herbert Screw

Abstract: Background: The Scaphoid bone is the tmost commonly fractured carpal bone. Proper clinical examination and radiological imaging is essential for early diagnosis and management. The management of scaphoid fractures varies from cast immobilization to open reduction and internal fixation. This paper explores the outcome of using headless cannulated screws in minimally displaced scaphoid fractures.Objective: Aim of this study is to assess the functional and clinical outcome of using cannulated headless screws in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…On the dominant side, 45% of the patients suffered fractures. Study by Gad, et al [13] found that the dominant right-side prevalence was 88.9%, which is consistent with our findings. All of the cases were recent fractures lasting less than three weeks.…”
Section: Discussionsupporting
confidence: 93%
“…On the dominant side, 45% of the patients suffered fractures. Study by Gad, et al [13] found that the dominant right-side prevalence was 88.9%, which is consistent with our findings. All of the cases were recent fractures lasting less than three weeks.…”
Section: Discussionsupporting
confidence: 93%